Analisis Karya Gambar Kuda Teknik Arsir Ditinjau Dari Komposisi, Proporsi dan Gelap Terang - Nova Aji Putra; Mesra Mesra (Mahesa Research Center, 2021)
This study aims to describe the tendency of arsir techniques from horse drawings and describe the application of the principle of fine art of horse drawing works. This research uses descriptive research design that is to describe research data as is. This research is focused on three aspects that are the basis of this research, namely the composition, proportions and dark aspects of light. The research population amounted to 73 works, the work of grade VII students A,B,C. Samples were taken with Random Sampling techniques, so that the class of 20 students was selected. So the sample of research as many as 20 works. Data collection in this research was conducted with observation and documentation techniques. The data were analyzed with descriptive analysis techniques, namely describing the composition, proportions and dark light used in the drawings of horses in grade VII SMP Swasta Pembangun Medan, Academic Year 2019/2020. The results of this study are as follows. (1) The composition applied obtains the